2014
DOI: 10.1016/j.vaccine.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The challenges and opportunities for the development of a T-cell epitope-based herpes simplex vaccine

Abstract: The infections with herpes simplex virus type 1 and type 2 (HSV-1 & HSV-2) have been prevalent since the ancient Greek times. To this day, they still affect a staggering number of over a half billion individuals worldwide. HSV-2 infections cause painful genital herpes, encephalitis, and death in newborns. HSV-1 infections are more prevalent than HSV-2 infections and cause potentially blinding ocular herpes, oro-facial herpes and encephalitis. While genital herpes in mainly caused by HSV-2 infections, in recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 100 publications
0
58
0
Order By: Relevance
“…Herpes simplex virus 1 (HSV-1) is one of the most successful human pathogens, infecting up to 80% of people worldwide (2,4,13,15,20). The HSV-1-derived tegument virion phosphoproteins (VPs), which are located between the capsid and the outer viral envelope proteins, contain a large number of possible protective CD8 ϩ T-cell epitopes (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herpes simplex virus 1 (HSV-1) is one of the most successful human pathogens, infecting up to 80% of people worldwide (2,4,13,15,20). The HSV-1-derived tegument virion phosphoproteins (VPs), which are located between the capsid and the outer viral envelope proteins, contain a large number of possible protective CD8 ϩ T-cell epitopes (11).…”
Section: Discussionmentioning
confidence: 99%
“…In HSV-seropositive SYMP individuals, sporadic reactivation of the virus from latency and its shedding in tears can cause blinding recurrent herpetic stromal keratitis (rHSK), a T-cell-mediated immunopathological lesion of the cornea (2,19,20). Vaccine clinical trials throughout the last 2 decades have concentrated on the antibody responses induced by HSV envelope glycoproteins gB and gD, which have failed to produce protective immunity (21,22).…”
mentioning
confidence: 99%
“…A staggering 1 billion individuals worldwide currently carry herpes simplex virus 1 (HSV-1) which causes a wide range of diseases throughout their lives (1)(2)(3)(4)(5). Following ocular or orofacial primary infection, HSV-1 establishes latency in sensory neurons of the trigeminal ganglia (TG) (6).…”
mentioning
confidence: 99%
“…Traditional vaccines, although protective against primary acute infection in mice, have failed therapeutically in clinical trials (15,16) One "common denominator" among previously failed clinical trials is that they used either the whole virus or whole HSV proteins (e.g., HSV glycoprotein D [gD]), which deliver protective epitopes, nonprotective epitopes, and maybe even pathogenic epitopes (i.e., infection-or disease-enhancing epitopes) (reviewed in reference 17). Thus, although these traditional vaccines were intended to target only HSV-specific protective immunity, antigen processing might have also generated HSV-derived epitopes that elicit nonprotective responses and possibly even harmful responses (1). We recently found that symptomatic (SYMP) patients (with a history of numerous episodes of recurrent ocular herpes disease) tend to develop CD8 ϩ T cells that strongly recognize a subset of HSV-1 gD epitopes that differs from HSV-1 gD epitopes that are strongly recognized by CD8 ϩ T cells from HSV-1-seropositive healthy asymptomatic (ASYMP) individuals (who have never had clinical herpes disease), and vice versa (1)(2)(3)(4)(5).…”
mentioning
confidence: 99%
See 1 more Smart Citation